California's Prisoner Protections for Family and Community Health Act: Implementing a Mandated Condom Access Program in State Prisons, 2015-2016. (July 2020) - Lucas, Kimberley D.; Bick, Joseph; Mohle-Boetani, Janet C.
In 2014, California passed Assembly Bill 966, which required condom access for persons incarcerated in all 35 California state prisons (33 men's and 2 women's prisons). The California Correctional Health Care Services and the Sexually Transmitted Disease Control Branch and the Office of AIDS of the California Department of Public Health collaborated in a prison administration–led multidisciplinary implementation workgroup. Our workgroup, representing public health, correctional health, legal and legislative affairs, labor relations, and prison staff members, participated in 4 planning meetings during May–September 2015. We surveyed prison staff members and incarcerated men to identify and address potential challenges; conceptualized a tamper-resistant condom dispenser; developed educational materials, frequently asked questions for staff members, and fact sheets for the public; and conducted forums for custody and medical staff members at each prison. Key lessons learned included the need for high-level custody support, engagement of labor unions early in the decision-making process, and flexibility within defined parameters for sites to determine best practices given their unique institutional population, culture, and physical layout. Condom access was initiated at 4 prisons in July 2015 and expanded incrementally to the remaining 29 men's prisons through July 2016. A total of 243 563 condoms were accessed in the men's prisons, for an average of 354 condoms per 1000 population per month. The start-up dispenser cost was $69 825 (735 dispensers at $95 each). We estimated an annual condom cost of $0.60 per person. Although staff members and incarcerated men expressed concern that this legislation would condone sex and provide repositories for contraband, no serious adverse incidents involving condoms were reported. California demonstrated that condom access is a safe, low-cost intervention with high uptake for a large correctional system and provided a replicable implementation model for other states. Prison condom programs have the potential to decrease transmission of sexually transmitted infections (STIs) among incarcerated persons and their communities, which are often disproportionately affected by STIs, HIV, and other chronic diseases.